<h3>
Answer:</h3>
<u>Given equation</u> :- 6m² + 7n
where,
- <u>Constant</u> = 0.
- <u>Variable</u> = m, n.
- <u>Terms</u> = 6m² , 7n.
9k2-12k+4
(k2-6k)+(-6k+4) factor out the 3k from 9k2 0 6k: 3k(k-2) factor out -2 from -6k +4n: -2 (3k-2) factor out common term (3k-2) = (3k-2 ) (3k-2) that equals (3k-2)2
Answer:
0, -2/3
Step-by-step explanation:
Answer:
its the last one
Step-by-step explanation:
Answer:
we have that
y < −3x + 3
y < x + 2
using a graph tool
see the attached figure
the answer is
the answer isThe point (1, −5) lie in the solution set